2015
DOI: 10.2106/jbjs.n.00665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Preconditioning Protocols on Anterior Knee Laxity After ACL Reconstruction with Four Commonly Used Grafts

Abstract: On the basis of these results, current preconditioning methods appear to be ineffective in reducing progressive increases in anterior knee laxity from cyclic loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Tibial osteotomies illustrate this concept as they do not fully eliminate cranial drawer, yet achieve successful outcomes. In man, laxity after ACL reconstruction has been attributed to creep relaxation in the ligament, inappropriate tension during fixation, and graft elongation during ingrowth of native cells . We do not believe that healing of the graft after our recheck at 12 months would improve the passive laxity detected in 3 stifles, all with less satisfactory outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…Tibial osteotomies illustrate this concept as they do not fully eliminate cranial drawer, yet achieve successful outcomes. In man, laxity after ACL reconstruction has been attributed to creep relaxation in the ligament, inappropriate tension during fixation, and graft elongation during ingrowth of native cells . We do not believe that healing of the graft after our recheck at 12 months would improve the passive laxity detected in 3 stifles, all with less satisfactory outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…4) ( Figure 1 ). Most recommended rehabilitation protocols after ACL reconstruction submit the neo-ligament to forces between 150 and 400N in the first 3 months, under the breaking limit of the construct tested in this study [ 10 ]. The breaking occurred at the suture wires as expected because this was the weakest material in our construct.…”
Section: Discussionmentioning
confidence: 99%
“…Andersen and Jorgensen determined that a significant decrease in knee motion occurred when the graft tension was N 33 N [24]. Boguszewski et al analyzed, in in vitro laboratory tests, the mechanical response of graft tissue for ACL reconstruction after different preconditioning protocols [25]. The authors subjected four commonly used grafts to a cyclic load of 89 N and showed no effect of the preconditioning compared to the no preconditioning condition on the anterior knee laxity.…”
Section: Discussionmentioning
confidence: 99%